Euroization of the Economy and the Negative Impact of the Strengthening of the Local Currency on Exports and Other Economic Indicators in Albania - Uldedaj, Gjokë; Beqaj, Besim; Kraja, Meri; Canka, Proc. Enxhi (Journal of Ecohumanism, 2024)
The Albanian economy is a small and open economy. As such, it is quickly influenced by the turbulence of the global, European, and regional economies. Economic theory emphasizes the link between the exchange rate, exports, the consumer price index, and the balance of foreign trade. The purpose of this article is to study the impact of the exchange rate, primarily at the export level, while also considering other economic factors within the framework of the overvaluation of the Albanian currency (ALL) against the currencies of partner countries, mainly the Euro. The overvaluation of the Albanian currency has led to discouraging exports and increasing imports, influencing the rise in the Consumer Price Index, meaning higher consumer prices. This is due to the fact that the Albanian economy is mainly dependent on imports. The empirical and econometric models used, along with the factors included in this study according to the hypotheses raised, are related to assessing the mutual relationships of the exchange rate with other economic factors for the time period 2018-2023.The results imply and depict the integrated relationship between the exchange rate and exports and other economic factors, as well as supporting the fact that the real exchange rate (RER) has deviated from its equilibrium level. The conclusions in this study confirm that an overvalued domestic currency has increased costs for operations conducted in the local currency ALL, reducing income for operations conducted in Euro and other currencies. This overvaluation of the domestic currency has resulted in losses for exporting companies, impacting the trade balance. Based on the findings in this study, it is crucial for financial institutions and policymakers to be consistent in monitoring the exchange rate, especially EUR/ALL, to improve the long-term relationships between the exchange rate, exports, and other economic factors.